Pytanie o klucz do teologii apostoła Pawła - Rakocy, Waldemar (Collectanea Theologica, 2016)
The author of the paper looks for a key to Pauline theology. Scholars differs considerably in this subject that results in sometimes extremely opposed views on the degree the old and new covenants are related to each other as well, as on to the degree Paul himself was linked to Judaism after his conversion. So far answers given by scholars focus on main themes of Paul’s Epistles (eschatology, soteriology and so on) or emerge from previous presumptions on Judaism, but not mainly from the Epistles themselves. The present article points at the concept of the new creation in Christ which is the background of all themes treated by Paul and links them in one coherent entity.